2014
DOI: 10.17221/270/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of the bacteriocin produced by Lactobacillus plantarum, isolated from Chinese pickle

Abstract: 119 strains of lactic acid bacteria from Chinese pickle were tested for production of antimicrobial compounds (bacteriocins). Among them, strain C8 showed strongly antibacterial activity against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739. Strain C8 was identified as Lactobacillus plantarum based on phenotypical, physiological tests and 16S rDNA identification. The antibacterial substance produced by strain C8 was sensitive to protease but not affected by lipase and amylase and designated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…VCO has been known for its high lauric acid content, which is between 46.36% and 48.42% [31] Processed from coconut milk, which is high in carbohydrates and proteins, the fermentation process of VCO results in lactic acid bacteria (LAB) [32][33][34][35]. LAB from VCO have been isolated and their antimicrobial ability also has been studied [36].…”
Section: Introductionmentioning
confidence: 99%
“…VCO has been known for its high lauric acid content, which is between 46.36% and 48.42% [31] Processed from coconut milk, which is high in carbohydrates and proteins, the fermentation process of VCO results in lactic acid bacteria (LAB) [32][33][34][35]. LAB from VCO have been isolated and their antimicrobial ability also has been studied [36].…”
Section: Introductionmentioning
confidence: 99%
“…This study clearly demonstrated that the BLS obtained from strain U10 is thermostable. Several studies have been reported that the BLS treated at 100°C for 60 min (Okpara et al 2014) and 121°C for 15 min were stable at this high temperature (Zhou et al 2014). This heat stability would be a very useful characteristic as antimicrobial peptide thermostable property in biomedicinal it could be used as antimicrobial peptide (Table 3).…”
Section: Characterization Of the Bacteriocinmentioning
confidence: 89%
“…It appeared despite the remaining LAB also that showed similar results after a catalase treatment by using Bacillus subtilis and Pseudomonas aeroginosa as indicator pathogens. Therefore, this study presumed that various antimicrobial activities attributed to each strain appeared due to the production of bacteriocins or metabolites similar to them into medium as natural defences or an adaptive response to surrounding environment (Zhou et al 2014). Antimicrobial activities of L. plantarum thus would be properly characterized by U10 strain isolate.…”
Section: Screening Of Potential Antimicrobial Lactic Acid Bacteriamentioning
confidence: 99%
“…LAB isolates grown in media without supplementation could not produce bacteriocins. ISSN 1978-3477, eISSN 2087 *Corresponding author: Phone: +62-24-8441555, Email: laksmi@unika.ac.id often regulated by some factors, such as growth pH, temperature, and nutrient sources (Mahrous et al 2013;Todorov and Dicks, 2005;Zhou et al 2014). Bacteriocin production requires suitable culture medium containing all essential nutrients in suitable amounts.…”
Section: The Effect Of Carbon and Nitrogen Supplementation On Bacterimentioning
confidence: 99%